18‐Crown‐6 Additive to Enhance Performance and Durability in Solution‐Processed Halide Perovskite Electronics. Issue 31 (7th July 2022) - Sim, Kihyung; Nakao, Takuya; Sasase, Masato; Iimura, Soshi; Kim, Junghwan; Hosono, Hideo
Abstract: Recently, an "interlayer" has been often adopted in organic–inorganic hybrid perovskite light‐emitting diodes (PeLEDs). The term "interlayer" infers that the layer function is not clear, but it improves electroluminescence (EL) performance. In this respect, it is of interest to determine the exact role of the interlayer and how it works in PeLEDs. In this study, the interlayer is determined to play a crucial role in suppressing the chemical reaction between the metal oxide and hybrid perovskite layers. Nevertheless, the use of an interlayer, a wide gap insulator, does not guarantee the best PeLED performance because it hinders charge injection into the emission layer. Here, a method is proposed that does not apply an "interlayer" but enables simultaneous attainment of high EL performance and outstanding device stability. 18‐crown 6‐ether (18C6) additive (2.5 mg mL −1 ) is found to fully suppress the chemical reaction between the metal oxide and hybrid perovskite layers. With the 18C6 additive, an 82‐fold longer device lifetime and very low operating voltage (3.2 V at 10 000 cd m −2 ) are demonstrated in a PeLED. Abstract : It is clarified that the mutual chemical reaction between metal oxide and organic–inorganic hybrid perovskite leads to poor electroluminescence performance and stability in perovskite light‐emitting diodes. It is revealed that 18C6 additive can fully suppress the chemical reaction between the two layers, making it possible to utilize both oxide electron transport layer and hybrid perovskite emission layer. A very low operating voltage of 3.2 V at 10 000 cd m −2 and enhanced thermal stability validate this study.